2016
DOI: 10.1021/acs.jpclett.6b01958
|View full text |Cite
|
Sign up to set email alerts
|

Carrier Decay Properties of Mixed Cation Formamidinium–Methylammonium Lead Iodide Perovskite [HC(NH2)2]1–x[CH3NH3]xPbI3 Nanorods

Abstract: Organic-inorganic lead iodide perovskites are efficient materials for photovoltaics and light-emitting diodes. We report carrier decay dynamics of nanorods of mixed cation formamidinium and methylammonium lead iodide perovskites [HC(NH)][CHNH]PbI (FAMAPbI) synthesized through a simple solution method. The structure and FA/MA composition ratio of the single-crystal FAMAPbI nanorods are fully characterized, which shows that the mixed cation FAMAPbI nanorods are stabilized in the perovskite structure. The photolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 58 publications
4
42
0
Order By: Relevance
“…By fine‐tuning key parameters, such as ligand concentration and injection temperature, MAPbI 3 nanosheets exhibited very long average lifetime (within 593 ns) in TRPL measurements, indicating that nearly defect‐free iodide‐based PNCs can be also obtained via effective surface passivation and dimensionality tuning . It is also interesting to observe that with mixed organic cations (e.g., FA x MA 1− x PbI 3 ) the PNCs show extremely long lifetimes for both radiative and nonradiative recombination, potentially allowing highly efficient charge transfer from excited state to charge acceptors (i.e., electron and hole transfer materials) if PNCs are used in solar cells . In fully inorganic lead PNCs such as CsPbX 3 , the PLQY dramatically fluctuates in a wide range closely dependent on the halide composition.…”
Section: Optoelectronic Propertiesmentioning
confidence: 99%
“…By fine‐tuning key parameters, such as ligand concentration and injection temperature, MAPbI 3 nanosheets exhibited very long average lifetime (within 593 ns) in TRPL measurements, indicating that nearly defect‐free iodide‐based PNCs can be also obtained via effective surface passivation and dimensionality tuning . It is also interesting to observe that with mixed organic cations (e.g., FA x MA 1− x PbI 3 ) the PNCs show extremely long lifetimes for both radiative and nonradiative recombination, potentially allowing highly efficient charge transfer from excited state to charge acceptors (i.e., electron and hole transfer materials) if PNCs are used in solar cells . In fully inorganic lead PNCs such as CsPbX 3 , the PLQY dramatically fluctuates in a wide range closely dependent on the halide composition.…”
Section: Optoelectronic Propertiesmentioning
confidence: 99%
“…Yang and co‐workers reported that the color of FAPbI 3 crystals gradually changed from black to yellow, regardless of storage in the vacuum or inert gas . Recently, the partial substitution of the FA cation has been reported to stabilize the perovskite phase of FAPbI 3 . However, this substitutional strategy also partially covers the properties of the FAPbI 3 material.…”
Section: Introductionmentioning
confidence: 99%
“…Such observation is in accordance with previous reports, where increased content of I − in MAPbI 3‐x Br x and insertion of water molecules in MAPbBr 3 systems result in diffraction peaks shifted to smaller 2θ angles. Although Se 2− ( r = 198 pm) has an ionic radius slightly smaller than I − ( r = 220 pm), it is still perfectly reasonable to result in an expanded perovskite lattice due to interstitial intercalation (instead of X‐site lattice points), and interstitial intercalation should leads to inefficient atomic packing, as in the cases of small alkali metal ion (Rb + , Li + , etc.) doped perovskite structures .…”
mentioning
confidence: 99%